PENERAPAN MODEL INQUIRY LEARNING TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN KEWARGANEGARAAN (PKN) DI KELAS VI SD NEGERI 043934 SIMPANG SINGA SEMESTER II T.P 2021/2022 - Kartini Sembiring (CV Putra Publisher, 2022)
This study aims to improve student learning outcomes by applying the inquiry learning model during teaching and learning activities in Civics Education (PKn) class VI SD Negeri 043934 Simpang Singa. The subjects in this study were Grade VI students of SD Negeri 043934 Simpang Singa with a total of 24 students. This study uses two cycles of action research. Each cycle consists of four stages, namely: design, activities and observations, reflection, and revision. The results of this study indicate that 1) Students' cognitive learning outcomes through the inquiry learning model in the subject of Citizenship Education (PKn) have succeeded in achieving completeness. In the first cycle, 9 students completed with an average of 63.33. In the second cycle, 21 students completed with an average of 83.33 and the class was completed. Completeness of cognitive learning outcomes occurs because in conducting group discussions, students are able to work well together; 2) Students' affectiveness through the inquiry learning model in the subject of Citizenship Education (PKn) has changed for the better in each indicator. This change occurs because the teacher provides motivation so that students improve their attitudes during learning; 3) Psychomotor students through the inquiry learning model in the subject of Citizenship Education (PKn) have changed for the better in each indicator. This change occurs because students have the courage to express their opinions and defend their arguments.